1997
DOI: 10.1080/02664769723729
|View full text |Cite
|
Sign up to set email alerts
|

Identification of outlier bootstrap samples

Abstract: We define a variation of Efron's method II based on the outlier bootstrap sample concept. A criterion for the identification of such samples is given, with which a variation in the bootstrap sample generation algorithm is introduced. The results of several simulations are analyzed in which, in comparison with Efron's method II, a higher degree of closeness to the estimated quantities can be observed.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
6
0

Year Published

2004
2004
2024
2024

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 1 publication
0
6
0
Order By: Relevance
“…As the number of unique items in a bootstrap sample is an important determinant of the behaviours of prediction rules learned on it, the distribution of this quantity should be of interest to researchers working on their development and validation. While related distributions have long been studied in a purer mathematical context [11], and this distribution has been identified before in this setting [16,1], nowhere were we able to find a concise and accessible summary of the relevant information for the benefit of researchers in machine learning. Our aim here is to fill this gap by presenting this distribution along with its key properties, and to make it easier for others who to understand or modify resampling techniques in a machine learning context.…”
Section: Introductionmentioning
confidence: 98%
“…As the number of unique items in a bootstrap sample is an important determinant of the behaviours of prediction rules learned on it, the distribution of this quantity should be of interest to researchers working on their development and validation. While related distributions have long been studied in a purer mathematical context [11], and this distribution has been identified before in this setting [16,1], nowhere were we able to find a concise and accessible summary of the relevant information for the benefit of researchers in machine learning. Our aim here is to fill this gap by presenting this distribution along with its key properties, and to make it easier for others who to understand or modify resampling techniques in a machine learning context.…”
Section: Introductionmentioning
confidence: 98%
“…Several empirical studies carried out in [7] showed closer estimations of the parameters under study and a reduction of the standard deviations of such estimations. These results were theoretically confirmed in [10].…”
Section: Reduced Bootstrapmentioning
confidence: 99%
“…However, this simulation process is affected by a series of errors and variabilities, as is formalized in [7]. For this reason, several alternative techniques have been proposed, as those recorded by [4], [8], [9].…”
Section: Reduced Bootstrapmentioning
confidence: 99%
See 1 more Smart Citation
“…The method is an extension of the one introduced by Muñoz-García et al [5], that takes k 2 = n. Note that ordinary bootstrap is a particular case of reduced bootstrap with k 1 = 1 and k 2 = n.…”
Section: Introductionmentioning
confidence: 99%